Geochemical processes in sulphidic mine tailings : field and laboratory studies performed in northern Sweden at the Laver, Stekenjokk and Kristineberg mine-sites - Holmström, Henning (Luleå tekniska universitet, 2000)
This thesis presents geochemical, mineralogical and laboratory studies of unremediated and remediated tailings at two abandoned mine sites; at Laver and Stekenjokk and at one active mine site; the Kristineberg mine. At Laver the Cu released from oxidation is enriched in an enrichment zone just below the oxidation front. Other sulphide bound metals seem to be more evenly spread over a greater volume of tailings and are mainly immobilised as a result of adsorption onto mineral surfaces. Adsorption is also important for Cu, but covellite (CuS) formation is more important, due to transformation of pyrrhotite (Fe1-xS). The groundwater within the impoundment at Laver is affected by the breakdown of sulphides during oxidation. Vertical flow of contaminated water is not the cause of groundwater contamination, since the metals are to a large extent retained in the tailings below the oxidation front. Instead, contamination occurs when the advancing oxidation front pushes the secondary enrichments of metals ahead to meet the groundwater table and the metals are released to the groundwater. The release of metals is caused by desorption due to the low pH in this environment. Areas of the tailings deposit with shallow groundwater table are at present the main sources of metal release. There is a seasonal variation in the composition of groundwater, particularly shallow groundwater, caused by changing levels of the groundwater table. Laboratory studies of the tailings from Laver and Stekenjokk using Humidity Cells tests show that the tailings at Laver are more reactive and have a higher oxidation rate compared with the tailings at Stekenjokk. This is probably due to the large carbonate content at Stekenjokk. The oxidation rate of the Stekenjokk tailings decreases with time, probably due to Fe-oxide-hydroxide coatings on sulphide surfaces. High pH conditions can be maintained and low metal concentrations are measured in the leachate waters. Diffusion of metals from the tailings up into the overlying pond water is occurring at ...